Ecotourism Based Sustainable Tourism Development - Anak Agung Ngurah Alit Wiraputra (Law Doctoral Community Service Journal, 2023)
Tourism is the activity of visiting a place as a journey from one place to another, which is temporary, carried out by individuals or a group as an effort to find balance or harmony and happiness with the environment in the Social, Cultural, Natural, and Scientific dimensions as well as various kinds of supported tourism activities. The aim research is to know the Ectourism Based Sustainable Tourism Development. This strategic approach to sustainable tourism is recommended for small-scale, local management, and benefits for the community. The result shows that with the implementation of tourism development programs that are made, regional development and the welfare of the people around the area will increase so that it can realize the vision of national tourism development, namely the realization of Indonesia as a world-class tourist destination country, competitive, sustainable, able to encourage regional development and people's welfare. The prominent supporters of the implementation of Ecotourism development have four elements that support the performance of the action, namely availability of adequate legal instruments, readiness of local government officials and institutions, availability of sufficient funds, community support in achieving goals.